Students’ Social-Emotional Integration: Teachers’ Attitudes Towards Successful of Inclusive Education - Prasetyo, Agung; Asrowi; Suryani, Nunuk; Sunardi (International Journal of Psychosocial Rehabilitation, 2020)
Positive attitudes become the essential part for the teacher to claim the successfulness of the inclusive education by giving the same rights and opportunities for the students with need to have the access as others. Referring to the quantitative data, it is rarely found the claim for its evidence to be explored in subject of academic or scientific field by empiric performance. This study exposed the link between teachers’ attitudes toward students’ social integration at inclusive schools by involving 10 Indonesian elementary schools and 20 teachers. Based on the schools report, it was stated that they did not apply any different treatment among their students who are with or without special needs (SN). Accessibility for any facilities and assistance were equally provided and given by the schools’ management. In contrary, SN students did not feel to be significantly socially included in their activities with non- SN classmates by not focusing and underlining the physical inclusion. Later, they expected a real and supporting of their teachers’ attitudes to be positive coming with positive effect. The gap between students with or without SN decreased significantly by perceiving the meaningful and stronger values of special education and inclusion. It is recommended for further research to focus on particular needs related to teachers’ attitudes and inclusive education.